Effects of standard diets from different sources on growth and some organ parameters of rats - GENC, B.; SALMAN, M.; TÜTÜNCÜ, Ş.; ERMIŞ, M.; MURUZ, H. (Journal of the Hellenic Veterinary Medical Society, 2020)
This study aims to determine the effects of open and closed formulated standard diets supplied from different sources on growth performance and internal organ development of laboratory rats. Five-week-old 32 Wistar rats were used. A special control group diet was produced in accordance with the criteria determined by the National Research Council (NRC) (1995). Three different most preferred commercial open and closed-formula diets produced by international and local companies were used as trial groups’ diets. The experiment was carried out for 12 weeks. Weekly feed consumption, body weight change, internal organ weight, intestinal organ weigths and lengths, intestinal villi heigth and crypt depth were measured in groups. The body weight values of the control group and the first group fed with open-formula diet were found at the highest level (P <0.05). The control group diet had a positive effect on small intestine villi heigth and crypt depth (P <0.05). The nutrient contents and energy values of the diets of experimental groups were determined as different from the commercial firm notifications. As a result of the research, it is concluded that the diets prepared with open-formula give more reliable results in the growth performance and development of internal organs of Wistar rats.